EU-AIMS Longitudinal European Autism Project (LEAP): the autism twin cohort - Isaksson, Johan; Bölte, Sven; Banaschewski, Tobias; Baumeister, Sarah; Brandeis, Daniel; Meyer-Lindenberg, Andreas; Mößnang, Carolin Ulrike; Ruggeri, Barbara; Tost, Heike (Molecular autism, 2018)
EU-AIMS is the largest European research program aiming to identify stratification biomarkers and novel interventions for autism spectrum disorder (ASD). Within the program, the Longitudinal European Autism Project (LEAP) has recruited and comprehensively phenotyped a rare sample of 76 monozygotic and dizygotic twins, discordant, or concordant for ASD plus 30 typically developing twins. The aim of this letter is to complete previous descriptions of the LEAP case-control sample, clinically characterize, and investigate the suitability of the sample for ASD twin-control analyses purposes and share some ‘lessons learnt.’ Among the twins, a diagnosis of ASD is associated with increased symptom levels of ADHD, higher rates of intellectual disability, and lower family income. For the future, we conclude that the LEAP twin cohort offers multiple options for analyses of genetic and shared and non-shared environmental factors to generate new hypotheses for the larger cohort of LEAP singletons, but particularly cross-validate and refine evidence from it.
Gesehen am 01.02.2021